Apobec-mediated retroviral hypermutation in vivo is dependent on mouse strain. - Hyewon Byun; Gurvani B Singh; Wendy Kaichun Xu; Poulami Das; Alejandro Reyes; Anna Battenhouse; Dennis C Wylie; Mario L Santiago; Mary M Lozano; Jaquelin P Dudley (PLoS Pathogens)
Replication of the complex retrovirus mouse mammary tumor virus (MMTV) is antagonized by murine Apobec3 (mA3), a member of the Apobec family of cytidine deaminases. We have shown that MMTV-encoded Rem protein inhibits proviral mutagenesis by the Apobec enzyme, activation-induced cytidine deaminase (AID) during viral replication in BALB/c mice. To further study the role of Rem in vivo, we have infected C57BL/6 (B6) mice with a superantigen-independent lymphomagenic strain of MMTV (TBLV-WT) or a mutant strain that is defective in Rem and its cleavage product Rem-CT (TBLV-SD). Compared to BALB/c, B6 mice were more susceptible to TBLV infection and tumorigenesis. Furthermore, unlike MMTV, TBLV induced T-cell tumors in B6 μMT mice, which lack membrane-bound IgM and conventional B-2 cells. At limiting viral doses, loss of Rem expression in TBLV-SD-infected B6 mice accelerated tumorigenesis compared to TBLV-WT in either wild-type B6 or AID-knockout mice. Unlike BALB/c results, high-throughput sequencing indicated that proviral G-to-A or C-to-T mutations were unchanged regardless of Rem expression in B6 tumors. However, knockout of both AID and mA3 reduced G-to-A mutations. Ex vivo stimulation showed higher levels of mA3 relative to AID in B6 compared to BALB/c splenocytes, and effects of agonists differed in the two strains. RNA-Seq revealed increased transcripts related to growth factor and cytokine signaling in TBLV-SD-induced tumors relative to TBLV-WT-induced tumors, consistent with another Rem function. Thus, Rem-mediated effects on tumorigenesis in B6 mice are independent of Apobec-mediated proviral hypermutation.